The persistence of potential: The life of Sir John B. Gurdon - Douglas A. Melton; Edward M. De Robertis (Proceedings of the National Academy of Sciences, 2026)
The death of Sir John Bertrand Gurdon in October 2025 marks the passing of one of the most influential biologists of the modern era. A developmental biologist, Sir Gurdon’s best-known experiments were performed with frog eggs and nuclear transfer, leading to discoveries that transformed our understanding of how genes control animal development and established the principles that underpin animal cloning, nuclear reprogramming, and regenerative medicine. These classical experiments paved the way for advances in induced pluripotent stem cells and energized thinking of new ways to treat diseases with cellular therapies. Sir John Gurdon’s legacy endures through his transformative discoveries, institutional leadership, and the scientists he inspired.